2021
DOI: 10.21608/jpp.2021.77256.1030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Classification of Yellow Maize Inbred Lines Using Line X Tester Analysis Across Two Locations

Abstract: Ten yellow maize inbred lines and three testers were top crossed in line × tester scheme in 2019 season. The resulted 30 top crosses with two check hybrids were evaluated at two locations in 2020 growing season to assess mean performance, general and specific combining ability and their interaction with locations as well as elucidate type of gene action. The recorded data were days to 50% silking, plant height, ear height, ear length, ear diameter, No. of rows/ear, No. of kernels/row and grain yield (ardab/fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
4
1
0
Order By: Relevance
“…These crosses could be chosen for development of maize hybrids to be used in NMBP. The results are in agreement with those obtained with by Vasal et al, (1992), Kanagarasu et al, (2010), Aly (2013), Yadav et al, (2020) and Ibrahim et al, (2021).…”
Section: Combining Abilities Effectssupporting
confidence: 93%
See 2 more Smart Citations
“…These crosses could be chosen for development of maize hybrids to be used in NMBP. The results are in agreement with those obtained with by Vasal et al, (1992), Kanagarasu et al, (2010), Aly (2013), Yadav et al, (2020) and Ibrahim et al, (2021).…”
Section: Combining Abilities Effectssupporting
confidence: 93%
“…The interactions of SCA x location were higher than GCA x location for all studied traits, except for EHT trait, indicating that the non-additive type of gene action was more effected by environmental changes than additive type of gene action. These results were supported the findings of Mosa (2017), Aly (2013), El-Gazzer et al, (2013), Ibrahim et al, (2021), and Mousa et al, (2021). The contributions of lines were higher than those of the testers for all studied traits, indicating that the line played an important role toward the improving of these traits.…”
Section: Genetic Parameters and Contribution Of Lt And L X Tsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results of GCA and SCA effects as additive and non-additive gene effects which played an important role in the inheritance for different traits of maize were reported by Chen et al, (2015), Dinesh et al, (2016, Monsif et al, (2018), Ilyas et al, (2019), El-Hefny et al, (2020, Mukhlif et al, (2020), Sayed et al, (2020), Abdulazeez et al, (2021), ALdulaimy and Hammadi (2021), Ibrahim et al, (2021), Kamara et al, (2021), Barzgari et al, (2022), Belay (2022), Ganapati Mukri et al, (2022), Sheikh Abdulla et al, (2022), and Zhang et al, (2022.…”
Section: Iv-specific Combining Ability (Sca)supporting
confidence: 77%
“…The low GCA to SCA variance ratio revealed the preponderance of non-additive gene action in the inheritance of grain yield (Kaur et al, 2010 andDinesh et al, 2016). Moreover, SCA could be used to predict the hybrid performance (Ibrahim et al, 2021). Moreover, Abrha et al, (2013) and Ganapati Mukri et al, (2022) reported that both of additive and nonadditive gene actions were important in controlling the behavior of genetic potential of the inbred lines of maize development for yield and related traits.…”
Section: Introductionmentioning
confidence: 99%